2015
DOI: 10.1016/j.compag.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Real-time approaches for characterization of fully and partially scanned canopies in groves

Abstract: Efficient information management in orchard characterization leads to more efficient agricultural processes. In this brief, a set of computational geometry methods are presented and evaluated for orchard characterization; in particular, for the estimation of canopy volume and shape in groves and orchards using a LiDAR (Light Detection And Ranging) sensor mounted on an agricultural service unit. The proposed approaches were evaluated and validated in the field, showing they are convergent in the estimation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 25 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…This issue was more severe when the model was created over the entire plant. The importance of segmenting the point cloud when applying the convex-hull algorithm to estimate volume was also evidenced by Auat Cheein et al [19].…”
Section: Modeling Of 3d Objects From the Point Cloudmentioning
confidence: 88%
See 1 more Smart Citation
“…This issue was more severe when the model was created over the entire plant. The importance of segmenting the point cloud when applying the convex-hull algorithm to estimate volume was also evidenced by Auat Cheein et al [19].…”
Section: Modeling Of 3d Objects From the Point Cloudmentioning
confidence: 88%
“…In order to compute the canopy volume, two main approaches are possible: either a discretization-based method in which small regular geometries are created inside the point cloud structure (occupancy grid approach) [6,7]; or a surface reconstruction method using triangulation of the outer points of the point cloud to represent the surface of the object. Auat Cheein et al [19] applied both the segmented convex-hull and the occupancy grid approaches in a point cloud from four pear trees and over a virtual template object. Both approaches proved to be effective on characterizing the tree canopies.…”
Section: Introductionmentioning
confidence: 99%
“…This study has demonstrated that it is necessary to scan with high point density without gaps due to the complex plant structure of cotton plants [38]. In addition, the dense point cloud could also be helpful for plant volume estimation using the partial scanned plants [32].…”
Section: Discussionmentioning
confidence: 99%
“…For some selected trees the volume estimation based on the 3D model was accurate-the correlation coefficient was up to 0.976 between LiDAR measurements and manual measurements-but the procedure of 3D model reconstruction was very time-consuming as several steps had to be carried out manually. Auat Cheein et al [32] compared four real-time canopy volume estimation approaches based on LiDAR data collected using the methodology [31] and 3D model reconstruction procedure. Results showed that the volume could be estimated using partially scanned canopies on either left or right sides.…”
Section: Introductionmentioning
confidence: 99%
“…Surface reconstructions based on enclosing objects (hull-based approach) were reported for orange 58 , olive 70 , pear, and apple trees 71 . Auat Cheein and Guivant 72 applied both the segmented convex hull and the occupancy grid approaches in a point cloud from four pear trees and over a virtual template object. Although a few drawbacks were pointed out, both approaches proved to be effective on characterizing the tree canopies.…”
Section: High-resolution 3d Modeling Of Tree Cropsmentioning
confidence: 99%